Langston Hughes's Poems As Manifestation of Racial Protest: Studi tentang Puisi-Puisi Langston Hughes sebagai - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
This is a study of Langston Hughes's poems presumably considered as manifestation of racial protest. Its main goal is to prove whether or not the above statement is true, and to examine the kinds of racial injustices Hughes's protest poems try to project. Conducted under the discipline of American Studieswhich employs interdisciplinary approach - historical, sociological, and literary ones, the research proves that the selected poems truly manifest racial injustices. The racism took the forms of racial discrimination, racial segregation, and racial lynching. The discriminating issues contained in the protest poems are about injustices in employment, African-American social life, and education. Racial segregation is ridiculed in poems representing the application of Jim Crow system and lynching is portrayed through the cruel treatment of the white mob toward the black victim who is hung to a crossroad tree. His indignation, however, does not drive him to conduct violent or destructive protest. In his own specific way, beside previous three discriminating issues, he rejects the ills of racism by composing poems about race pride and African-American greatest expectation which he covers in poems about African-American dreams. In grace, he points out the good sides of his community as well as his pride as both an African-American and an American citizen. He truly believes that the blacks in America, well-known as "homeland of the free", still have better future, equal rights and opportunity to achieve their goals, and to realize the African-American dreams.